Classification of honey from its bee origin via chemical profiles and mineral content - Kek, Siok Peng; Chin, Nyuk Ling; Tan, Sheau Wei; Yusof, Yus Aniza; Lee, Suan Chua (Springer Verlag, 2017)
Raw honeys from four different bee species, namely the honey bees and stingless bees, were classified based on its chemical profiles, mineral contents and heavy metals. Chemical profiles including proximate composition, predominant sugars, hydroxymethylfurfural content, and diastase activity were determined following official methods while mineral and heavy metals contents were obtained from atomic adsorption spectrometry (AAS) and inductively coupled plasma-mass spectrometry (ICP-MS) measurements, respectively. Both hierarchical cluster analysis and principal component analysis show high possibility of distinguishing honey by its bee species of honey bees (Apis spp.) and stingless bees (Heterotrigona itama) based on distinctive differences in chemical compositions and mineral contents. Potassium and sodium were the major elements in raw honey samples at average of 904.9 and 617.6 mg/kg, respectively. Honey from stingless bee contained more protein, 0.85 g/100 g and less total sugar of fructose and glucose at 24.99 g/100 g. The information of bee speciation origin of honey bees and stingless bees enhances the identity of honey on the product labelling.